Production of IN718 superalloys by powder injection moulding - (:unkn) unknown (European Powder Metallurgy Association (EPMA), 2012)
This study aimed to determine optimum sintering parameters of IN718 superalloy powder parts which are shaped by the Powder Injection Moulding (PIM) method. At initial stage IN718 powder was mixed with a multi-component binder system. The resulting mixture was granulated and injected as standard tensile bar form. After moulding IN718 specimens were subjected to debinding process which consists of solvent debinding and thermal debinding steps. To determination of sintering temperatures, debinded samples were subjected to Differential Scanning Calorimetry (DSC) and dilatometer analyses, and then they were sintered at various temperatures under high level vacuum. After sintering, density measurements and optical microscope examinations were performed. Sintered density values have increased depending on increasing of sintering temperature. The highest density value was determined for the sample which sintered at 1290 °C.
Keywords: IN718; Microstructure; Powder injection moulding; Sintering; Superalloy